The evolution of prophylactic neck irradiation in nasopharyngeal carcinoma: Changing concepts and irradiation ranges - Wenjun Liao; Yue Zhao; Shichuan Zhang (Precision Radiation Oncology)
Abstract The approach to prophylactic neck irradiation in nasopharyngeal carcinoma (NPC) has undergone significant changes. For decades, prophylactic whole‐neck irradiation has been the standard for all patients with NPC; however, it is linked to a high risk of late complications. Advances in imaging modalities have deepened understanding of the metastatic characteristics of the cervical lymph nodes (LN), prompting a shift towards sparing the uninvolved lower neck and medial retropharyngeal nodal region. This targeted approach has proven effective in controlling cervical LN recurrence as whole‐neck irradiation while significantly reducing adverse effects. Currently, contouring of the neck lymphatic drainage clinical target volume (CTV) is being explored to eliminate the use of uniform cervical LN levels as a delineation boundary. Instead, the inferior boundary of the neck CTV is determined either by the distance from the lowest positive LN or two cervical vertebrae below the lowest positive LN, facilitating more individualized CTV delineation and prophylactic neck irradiation. Additionally, omitting lower‐risk neck lymphatic drainage CTVs and irradiating only visible LNs in these areas are also being explored. This review examines the evolution of prophylactic neck irradiation for NPC, providing key insights into these advancements.